Рыбец Vimba vimba vimba natio carinata (Pall.) в Каховском водохранилище - Белый, Н.Д. (Вестник зоологии, 1969)
It is established that the periods of spring migration of V. v. v. natio corinata in the Kakhovka reservoir and the Lower Dnieper coincide. V. v. v. natio corinata from the Lower Dnieper before spawning might pass through sluices and get to the reservoir. But V. v. v. natio corinata from the Kakhovka reservoir could preserve the property to realize the spawning migration in definite periods. Age composition of puberal V. v. v. natio corinata schools from the reservoir and Lower Dnieper is similar, but the fertility of the latter is half as high as that in the reservoir. Out of 22 comparable plastic characters of V. v. v. natio corinata from the re servoir and Lower Dnieper the ratio of the difference of means to the mean error of this difference (M. diff.) by nine characters surpasses 3, which evidences for a great diffe rence of variation series of characters or for a real difference of characters. The data presented give the grounds to suppose that among V. v. v. natio corinata in the Kakhovka reservoir there might be nat only the fish coming from the Lower Dnieper but also the individuals grown in it from the spawn.